The Community Participation in the Implementation of Diversion at Investigation Level - Rahmawati, Dian; Bawono, Bambang Tri (Universitas Islam Sultan Agung, 2021)
This study aims to determine the role of the community in the implementation of diversion at the level of investigation that is important as a way of resolving cases of children who are in conflict with the law. This research was carried out in the city of Semarang, Central Java by selecting institutions relevant to the problem in this journal, namely the Class I Penitentiary Semarang by using a research method in the form of the Sociological Juridical method. The research specifications used were descriptive analytical. The data sources were obtained from primary data sources and secondary data with data collection carried out by means of field studies by conducting interviews supported by literature studies. From the research conducted, the authors get the following results, The role of community members in implementing diversion is very important because apart from being mandated by Act No. 11 of 2012, community members also implement Community Based Corrections (CBC); community participation can increase the effectiveness and efficiency of the settlement of children's cases; Community participation in the implementation of diversion is an effort to protect children and protect the community itself.